Pilgrimage and power: the Kumbh Mela in Allahabad, 1765-1954 - Maclean, Kama (Oxford University Press, 2008)
Kama Maclean covers the Kumbh Mela in Allahabad, India, which is not merely a major Hindu religious pilgrimage but the largest religious gathering in the world.